2019
DOI: 10.1101/580969
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hi-C guided assemblies reveal conserved regulatory topologies on X and autosomes despite extensive genome shuffling

Abstract: Genome rearrangements that occur during evolution impose major challenges on regulatory mechanisms that rely on three-dimensional genome architecture. Here, we developed a scaffolding algorithm and generated chromosome-length assemblies from Hi-C data for studying genome topology in three distantly related Drosophila species. We observe extensive genome shuffling between these species with one synteny breakpoint after approximately every six genes. A/B compartments, a set of large gene-dense topologically asso… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…In fact, TADs generally overlap with syntenic blocks, i.e. regions of DNA with conserved collinearity of genes and/or non-coding elements, and syntenic rearrangement breakpoints are enriched at TAD boundaries both in vertebrates and flies [45][46][47][48][49] . However, this overlap might simply be the consequence of TAD boundaries' relative "fragility" to double-strand breaks (DSB).…”
Section: /15mentioning
confidence: 99%
“…In fact, TADs generally overlap with syntenic blocks, i.e. regions of DNA with conserved collinearity of genes and/or non-coding elements, and syntenic rearrangement breakpoints are enriched at TAD boundaries both in vertebrates and flies [45][46][47][48][49] . However, this overlap might simply be the consequence of TAD boundaries' relative "fragility" to double-strand breaks (DSB).…”
Section: /15mentioning
confidence: 99%
“…Interactions between TADs contribute to higher level, hierarchical genome organization [12]: multiple TADs within each compartment and multiple compartments within each chromosome territory. Boundaries between individual TADs are conserved among cell types and sometimes across species [13,14,15,16,10,17,18]; this feature makes TAD a natural structural unit of chromatin useful for modeling purposes and reasoning [19,20], including in this work. TADs interact among themselves forming dynamic, relatively short-living 3D-structures, that segregate chromatin into mutually excluded active (type A) and inactive (type B) compartments [21,12].…”
Section: Introductionmentioning
confidence: 99%
“…The chromosome architecture supports local interactions between HASs and neighboring active genes, which facilitates the spread of DCC complexes to the regions containing genes whose transcription should be increased in males(88,93). A comparison of the X chromosome architecture in distant Drosophila species showed that spatial contacts with potential HAS regions are conserved, despite the existence of a large number of genomic rearrangements between the studied species(94). The C2H2 proteins that interact with MSL1 and CLAMP are likely to contribute both to distance interactions between HASs and genes and to the formation of secondary (weak) MSL recruitment sites at target genes.…”
mentioning
confidence: 70%